Profile analysis of young adults seeking addiction treatment - Selma Ósk Höskuldsdóttir 1986- (2021)
The aim of this study was to gain a better understanding of the characteristics of young adults seeking addiction treatment in Iceland. Data were drawn from medical records of all consecutive hospital admissions of 148 patients entering specialized treatment for young adults, age 18-26, over six months. Findings showed that young people who seek addiction treatment at Vogur Hospital bring with them a range of complex needs, mainly social, substance use, and mental health issues. Most participants had only completed compulsory education and only a third were employed. Furthermore, young adults with the most re-admissions had a more serious demographic profile than those with fewer admissions. These young adults have a severe addiction, and the majority were diagnosed with poly-substance use, with cannabis dependence being the most common primary diagnosis. Many reported having overdosed, and a history of psychiatric problems was common. Almost two-thirds reported a confirmed psychiatric diagnosis, and over one-third had a history of receiving child and adult psychiatric services. The majority of young adults reported self-harm behavior, and almost half reported suicide attempts. This study provides a unique socio-demographic profile, substance use and treatment pattern, and psycho-social profile of young adults who seek addiction treatment at Vogur Hospital. Study results implicate the need for more holistic- and individualized treatment and support following treatment completion to better meet the needs of many treatment-seeking young adults. Keywords: addiction treatment, young adults, profile, mental health